Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


First find out the roots alpha and beeta . Then  (a+b)^{2} -2ab(a+b) A+b is sum of the roots -b/a and ab is product of the roots ab=c/a substitute in the relation and find out the ans

2 5 2
X²-5x+6 = 0
x²-3x-2x+6 = 0
x(x-3)-2(x-3) = 0
(x-2)(x-3) = 0
the zeroes are 2 and 3
α²+β² = 4+9 = 13
1 3 1
that's not the way you answer...
you must substitute the value -b/a and c/a and then calculate
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts